Barriers and enablers to diabetic retinopathy screening attendance: Protocol for a systematic review. Issue 1 (December 2016) - Graham-Rowe, Ella; Lorencatto, Fabiana; Lawrenson, John; Burr, Jennifer; Grimshaw, Jeremy; Ivers, Noah; Peto, Tunde; Bunce, Catey; Francis, Jill
Abstract Background Diabetic retinopathy is a serious complication of diabetes which, if left untreated, can result in blindness. Population screening among people with diabetes has been shown to be clinically effective; however, suboptimal attendance with wide demographic disparities has been reported. To develop quality improvement interventions to maximise attendance, it is important to understand the theoretical determinants (i.e. barriers and enablers) of screening behaviour. The aim of this systematic review is to identify and synthesise the modifiable barriers and enablers associated with diabetic retinopathy screening attendance. Methods/design Primary and secondary studies will be included if they report perceived barriers/enablers of diabetic retinopathy screening attendance, from the perspectives of people with diabetes and healthcare providers. There will be no restrictions on study design. Studies will be identified from published and grey literature through multiple sources. Bibliographic databases will be searched using synonyms in four search domains: diabetic retinopathy; screening; barriers/enablers; and theoretical constructs relating to behaviour. Search engines and established databases of grey literature will be searched to identify additional relevant studies. Extracted data will include: participant quotations from qualitative studies, statistical analyses from questionnaire and survey studies, and interpretive descriptions and summaries of results from reports. All extracted data will be coded into domains from the Theoretical Domains Framework (TDF) and (for organisational level data) the Consolidated Framework of Implementation Research (CFIR); with domains representing theoretical barriers/enablers proposed to mediate behaviour change. The potential role of each domain in influencing retinopathy screening attendance will be investigated through thematic analysis of the TDF/ CFIR coding. Domain importance will be identified using pre-specified criteria: "frequency" and "expressed importance". Variations in perceived barriers and enablers between demographic groups (e.g., socio-economic, ethnic) will be explored. Discussion This review will identify important barriers and enablers likely to influence attendance for diabetic retinopathy screening. The results will be used to assess the extent to which existing interventions targeting attendance address the theoretical determinants of attendance behaviour. Findings will inform recommendations for future intervention design. Systematic review registration PROSPEROCRD42016032990